How Authoritarian Rulers Seek to Legitimise Repression: Framing Mass Killings in Egypt and Uzbekistan - Mirjam Edel; Maria Josua (German Institute of Global and Area Studies (GIGA), 2017)
How do authoritarian rulers legitimate repressive actions against their own citizens? Even in autocracies with limited accountability, discursive justifications are often put forward to decrease the costs of domestic repression. Although the research depicts state repression as the opposite of legitimation, justified coercion against some groups may generate legitimacy in the eyes of other parts of the population. This paper conceptualises the suggested links between legitimation and repression. It studies the justifications of mass killings by integrating framing theory with recent research on the domestic and international dimensions of authoritarian rule. Given the common threats at the global level and the diffusion of repressive tactics, we assume that discursive justifications of repression in authoritarian regimes change over time, probably due to learning processes. We compare Egypt and Uzbekistan to analyse the government rhetoric in the Rabi'a and Ferghana Valley protest crackdowns, respectively, taking into account the audiences of the framing and the sources of the frames that justify repression.
Keywords: 300; authoritarianism; protests; repression; state-society relations; framing